Sistem Kompensasi : Komponen, Prinsip dan Tujuannya - Yudha Nata Saputra (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Employees are one of the company's assets, their position is very important in order to advance the company, so companies need to pay attention to their employees. On the other hand, employee performance itself will be determined by employee job satisfaction with the company, so paying attention to employee job satisfaction becomes important in order to improve company performance. Among the many factors that influence employee job satisfaction, inflation is one factor that has a fairly strong influence on job satisfaction. In Indonesia, cases of industrial disruption tend to remain high, one of which is caused by problems with the settlement system implemented by companies which are not in line with expectations. This situation shows that the settlement system for related components, the principles and objectives of providing compensation have not been properly understood. Compensation as a system consisting of salaries, incentives and allowances received by employees, each component according to its characteristics has principles that need to be followed. Meanwhile, the objectives of providing compensation include getting quality employees, retaining existing employees, ensuring equality, providing an imbalance that meets expected behavior, controlling costs and complying with applicable laws and regulations.